Alternatif Pemecahan Masalah Dengan Menggunakan Pendekatan Sistem di MIS Nurul Fadhilah - Tarisa Munawwarah; Nur Alfiana Kholizah; Dinda Aulia Sani; Fathia Hanifah; Intan Savitri; Maulida Yani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In an educational institution, problems will definitely occur, both internal and external. In solving these problems, it would certainly be more effective if there was a system approach to problem solving in an educational institution. The systems approach is useful for what alternatives will be applied to problem solving which might guide leaders and educators in solving problems. Through research using this qualitative method, the author can describe the systems approach in solving problems through interviews with the principal of MIS Nurul Fadhilah. With sufficient research time to be able to analyze things related to the systems approach to solve problems or simplify problems that occur at the Nurul Fadhilah MIS school.